Laying the foundation for high performance of new digital logistics ventures - Schwemmer, Martin; Roth, Angela; Pflaum, Alexander (International Journal of Business and Systems Research, 2021)
New ventures can have a crucial effect to infuse innovation into an industry. The recent emergence of new logistics ventures can be identified as a relevant trend. Taking into account digitalisation, this study analyses, how new logistics ventures can lay the foundation for high performance in a digital environment at an early stage of existence. The chosen research approach combines secondary data collection and an interview study following the principles of grounded theory. The sample is composed of founders, investors, corporate investors and consultants from Central Europe experienced in the area of interest. As a result, ten propositions for new venture performance in a digitalising environment are presented and discussed. These propositions can be categorised in four dimensions: entrepreneurial team, entrepreneurial resources, entrepreneurial opportunity, and strategic and organisational fit. Likewise, these propositions constitute a shortlist of what is relevant to lay the foundation for high new digital logistics venture performance.<br
Keywords: logistics startups; new ventures; logistics; supply chain management; logistic entrepreneurship